Description of the snail-eating flatworm in marine aquaria, Pericelis tectivorum sp. nov. (Polycladida, Platyhelminthes) - Dittmann, Isabel L.; Dibiasi, Wolfgang; Noreña, Carolina; Egger, Bernhard (Zootaxa, 2019)
We describe a new marine snail-eating flatworm, Pericelis tectivorum sp. nov., found in coral-bearing marine aquaria. Pericelis tectivorum sp. nov. is characterised by several differential characters of the external and internal morphology like 1) a long line of frontal eyes extending anteriorly; 2) the length of the penis papilla; 3) the spherical seminal vesicle; 4) the lack of the enlargements of the ejaculatory duct; 5) the uterine vesicles, which start posterior of the female genital at the level of the sucker and 6) the distinct sucker. The combination of these characters in one species is unique and therefore the studied specimens are recognised by us as a new species. We additionally present a phylogenetic reconstruction using partial 28S rDNA sequences including three congeners. Our analysis demonstrates that P. tectivorum sp. nov. differs also genetically from other Pericelis species included in this analysis.